The effectiveness of an innovative leadership development program for primary school administrators - Yupadee Aekbua; Piangkae Poophayang; Terdsak Suphandee (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
The purpose of this research was tostudy the effectiveness of innovative leadership development program for primary school administrators. The research methodology can be summarized as follows: 1) the results of the effective implementation of the innovative leadership development program by selected 20 school administrators for the 2023 academic year, employing a specific selection process and voluntary participation development; 2) the results of the evaluation of the effective innovative leadership development program of school administrators in primary schools were evaluated by 9 experts and stakeholders. The statistics used in data analysis include percentage, mean, standard deviation, and the t-test statistics. The results showed that the participants had a higher development. They had the satisfaction of using the program in all aspects at the highest level.